THE LEGAL NATURE OF THE USE OF COMPULSORY MEDICAL MEASURES AGAINST PERSONS SUFFERING FROM ALCOHOLISM, DRUG ADDICTION OR INTOXICATION - Ermatov Gayratjon Okmirzaevich (International Journal of Business, Law and Political Science, 2024)
This article describes the issues related to the improvement of the institution of coercive measures in the medical field and the regulation of its legal bases, and the normative legal documents in this regard are analyzed. Also, the grounds for imposing coercive medical measures by the court against a person who has committed a dangerous act, the goals and types of coercive medical measures, the general grounds for applying these measures, their appointment, extension, modification and termination, as well as coercive medical measures prescribed with punishment application rules are defined. Committing a socially dangerous act by a person in a state of mental insanity or whose mental state is disturbed in a way that does not exclude sanity, as well as addicted to alcohol, drugs or intoxication, threatens the violation of the rights and freedoms of other persons, the interests of society and the state, the natural environment, peace and human security